A Study on the Contribution of Language Day Programs to Vocabulary Mastery in a Dormitory Setting - Lusi, Lusiana; Nunun Indrasari; Istiqomah Nur Rahmawati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
The problem identified in this study is that the majority of students expressed difficulty in using vocabulary appropriately, especially in distinguishing nuances of meaning between vocabulary that have the same meaning. The purpose of this study is to analyze the impact of the Language Day Program on students' vocabulary mastery in Islamic universities in Lampung by examining internal and external factors and knowing students' attitudes towards the program based on the ABC Model (Affective, Behavioral, Cognitive). The method used is descriptive qualitative with a case study approach. The data collection used was observation, interview, and documentation and used purposive sampling. The results show the positive impact of the program; internal factors such as increased learning motivation, active participation, self-confidence, and vocabulary mastery encourage students to express ideas more freely. External factors such as the teacher's role as a facilitator help students use vocabulary appropriately, contextually, and naturally. Effectively, students showed a positive emotional response to the program. Behaviorally, students actively used the new vocabulary, although the consistency varied. Cognitively, students felt the program improved their understanding of vocabulary and language context, although they still had difficulty in distinguishing similar vocabulary. The program needs to optimally apply the principles of CLT, namely exposure to the use of native speakers' mother tongue and the importance of games in learning, to maximize the improvement of vocabulary mastery. Further research is also needed to explore other factors besides vocabulary and develop more effective teaching strategies.